Voriconazole treatment of Candida tropicalis meningitis: persistence of (1, 3)-β-D-glucan in the cerebrospinal fluid is a marker of clinical and microbiological failure. Issue 31 (August 2016) - Ceccarelli, Giancarlo; Ghezzi, Maria Cristina; Raponi, Giammarco; Brunetti, Grazia; Marsiglia, Carolina; Fallani, Stefania; Novelli, Andrea; Venditti, Mario
Abstract: Introduction: Infections are still the most common complications of cerebral shunt procedures. Even though fungal etiologies are considered to be rare, they are associated with significant morbidity and mortality. Due to their uncommonness, diagnostic procedures and optimal therapy are poorly defined. We report a case of Candida tropicalis infection of ventriculo-peritoneal cerebrospinal fluid (CSF) shunt in a 49-year-old immune competent male treated with voriconazole (VOR). Methods: Microbiological and CSF markers (1, 3-b-D-glucan-BDG) of fungal infection, biofilm production capacity, sensitivity of serial isolates of the pathogen, and the concentration of the antifungal drug have been monitored and related to the clinical course of this infection. Results: Despite appropriate treatment with VOR, in terms of adequate achieved CSF drug concentrations and initial effective therapeutic response, loss of VOR susceptibility of the C tropicalis and treatment failure were observed. Conclusion: Biofilm production of the C. tropicalis isolate might have had a significant role in treatment failure. Of interest, clinical and microbiological unfavorable outcome was anticipated by persistence of BDG in CSF. Rising titers of this marker were associated with relapse of fungal infection.